Steady Flow of a Power Law Fluids with Uniform Suction and Injection between Given Two Parallel Plates: Investigation of Power Law Fluid Flow Decoration under Uniform Suction and Injection between Parallel Plates (Journal of Advances and Scholarly Researches in Allied Education, 2019)
My study is about the flow of a non-Newtonian power law fluid between two immovable parallel plates. The flow of power law fluid is encountered in various Industrial Technological areas. A uniform suction and injection through the surface of the parallel plates are applied where the two plates are kept at different but constant temperature and pressure. Numerous of study are focussed on the investigation of flow. However, these studies are bounded to the consideration of the non-Newtonian fluid behaviour. They leave the viscous dissipation out of description. The research facts on the power law fluid flow with allowance for the diffraction are presented. The aim of this study work is to analyse the power law fluid flow decoration or influence under uniform suction and injection between two parallel plates, And for this, here we assumed carry it some certain equation, and we will find the velocity profiles at different cases.